Technological aspects of the robotic TOPTIG surfacing of boiler steel tubes using alloy inconel 625 - Pfeifer, T.; Rozanski, M.; Grobosz, W.; Rykala, J.; Riabcew, I.A. (Автоматическая сварка, 2017)
The research aimed to develop technological parameters of the TOPTIG method-based surfacing (using alloy Inconel 625) of boiler tubes (O 45x5) made of steel 13CrMo4-5 ensuring the obtainment of the iron content on the overlay weld surface below 5%. The research resulted in the development of sets of parameters enabling the obtainment of overlay welds characterised by very high quality and the minimum degree of the stirring of the overlay weld metal with the base material. The above named sets of parameters were utilised when making a number of overlay welds on tubes. The research involved macroscopic metallographic tests of overlay welds, the identification of the base material content in the overlay weld, the determination of the chemical composition of the overlay weld surface as well as the performance of microscopic metallographic tests and the microanalysis of the chemical composition. It was ascertained that the TOPTIG technology enabled the making of overlay welds characterised by very high quality and the minimum degree of the stirring of the overlay weld metal with the base material (only 3.28%) and made it possible to obtain an iron content of 2.75% on the overlay weld surface using forced cooling performed inside the tube. Surfacing without cooling led to a significantly higher base material content in the overlay weld (approximately 14%), where the content of iron on the overlay weld surface amounted to 8.47%.